STRENGTHENING BALI TRADITIONAL LAW THROUGH WRITTING CUSTOMARY LAW OF TRADITIONAL VILLAGE - I Ketut Kasta Arya Wijaya; I Wayan Arthanaya; Ni Putu Sawitri Nandari; Suwitra, I Made; I Wayan Wesna Astara (Journal Equity of Law and Governance, 2021)
The formulation of customary law norms for marriage and inheritance needs to be constructed through Awig-Awig (customary law) formulation to ensure legal certainty in strengthening Balinese customary law. The Awig-Awig formulation is a form of codification of Balinese customary law, which regulates traditional village members and their various activities, Parhyangan (temple) as a forum for village members to connect with Ida Sang Hyang Widi Wasa (God Almighty) and at the same time as a means of preserving Balinese culture, Palemahan (land) as a manifestation of the territory and at the same time as an area that becomes the foundation of the source of life and a foothold in living life until death in a harmonious relationship. In the development of the life of village members, which are always in process, it is necessary to confirm the arrangement through Awig-Awig formulation, such as in the field of membership of village members with their rights and obligations, marriage, inheritance with the intention of being enforced consistently and dynamically according to appropriate values ​​in a society that is always developing.